Students’values and their Mental Health During Pandemic - Kamila, Aliyeva (2021)
Values are widely studied concept by many researchers  trying to explore how basic values influence the way individuals think, feel and behave (Durkheim, 1964; Weber, 1958; Hitlin & Piliavin, 2004; Rohan, 2000; Schwartz, 1992; Smith & Schwartz, 1997; Schwartz, 2006; Williams, 1968). Values are playing crucial role in the formation of individuals’ personality and this influence can be better explained by the components of these values which consist of how student perceive the reality, what they know, how they feel and the way they react to various situations.  Taken together these components help to form certain attitudes toward different objects, other people and situations and serve as a basis for students’ motivation. Therefore, by influencing the attitudes and motivations of individuals values are having various consequences. The current study attempted to understand some of the psychological consequences of values on students’ mental health.  The results of the study show that there are value differences for male and female students. In addition, the degree of anxiety and depression was assessed, and statistical analysis of the data shows that females are more anxious (F=0.24, p < 0.001) and depressed F=8.04 (p< 0.001) compared to male students and these differences were found to be statistically significant.Conformity, tradition, universalism, and power values were greater for females compared to males and these differences were statistically significant. Self-direction value was found to be more important to male students compared to female students and the difference was statistically significant. These findings lead to the conclusion that values that are having greater importance for females could be one of the factors contributing to their level of anxiety and depression while values being important for male students could be the factor helping them to cope with stressful situations. The development of further research would be suggested to explore the contribution of certain values to the level of anxiety and depression for students with more diverse and large sample.